2022
DOI: 10.3389/fmicb.2022.1023315
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides fragilis derived metabolites, identified by molecular networking, decrease Salmonella virulence in mice model

Abstract: In the gut microbiota, resident bacteria prevent pathogens infection by producing specific metabolites. Among bacteria belonging to phylum Bacteroidota, we have previously shown that Bacteroides fragilis or its cell-free supernatant inhibited in vitro Salmonella Heidelberg translocation. In the present study, we have analyzed this supernatant to identify bioactive molecules after extraction and subsequent fractionation using a semi-preparative reversed-phase Liquid Chromatography High-Resolution Tandem Mass Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
1
1
0
Order By: Relevance
“…These results were not surprising as it was described by [49] that Bacteroides regulate bile acid metabolism by converting taurochenodeoxycholic acid to lithocholic acid, which activates G protein-coupled bile acid receptor-1 (TGR5) to stimulate GLP-1 secretion from L cells [49]. B. fragilis that we used in this study produced bile acids after growing in cell culture medium containing fetal bovine serum [50,51]. Interestingly, it was also reported that C57BL/6J mice reconstituted with Bacteroides acidifaciens had increased GLP-1 [52].…”
Section: Discussionsupporting
confidence: 73%
“…These results were not surprising as it was described by [49] that Bacteroides regulate bile acid metabolism by converting taurochenodeoxycholic acid to lithocholic acid, which activates G protein-coupled bile acid receptor-1 (TGR5) to stimulate GLP-1 secretion from L cells [49]. B. fragilis that we used in this study produced bile acids after growing in cell culture medium containing fetal bovine serum [50,51]. Interestingly, it was also reported that C57BL/6J mice reconstituted with Bacteroides acidifaciens had increased GLP-1 [52].…”
Section: Discussionsupporting
confidence: 73%
“…Two species, Bacteroides fragilis and Bacteroides ovatus , were also detected with a reduction in rats with SBS. As a part of the commensal gut flora, the benefits of Bacteroides fragilis , including preventing pathogens colonization and translocation, restoring gut barrier integrity and maintaining microbial balance, have been determined in mounting studies ( Deng et al, 2018 ; Gautier et al, 2022 ). Furthermore, our analysis showed enrichment of Akkermansia muciniphila in Sham rats, which was proposed to be a contributor to metabolic heath and intestinal adaptive immune responses ( Dao et al, 2016 ; Ansaldo et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%